Spatial mineral chemistry of volcanic rocks from the Karacadağ Volcanic Complex and Karapinar Volcanic Field (Central Anatolia): evidence for a trans-crustal magmatic system - Gençoğlu Korkmaz, Gülin; Kurt, Hüseyin; Asan, Kürşad; Petrelli, Maurizio; Leybourne, Matthew (Mineralogy and petrology, 2025)
This research investigates the trans-crustal magmatic evolution of the Karacadağ Volcanic Complex (KCVC)-Karapınar Volcanic Field (KPVF) in Central Anatolia, with a particular focus on the major and trace element compositions of clinopyroxene and amphibole minerals from basaltic and andesitic lavas. Pliocene-aged Karacadağ andesites and Quaternary-aged Karapınar basalts contain various crystal cargoes, including crystal clots, several types of enclaves, xenocrysts, autocrysts, and antecrysts, suggesting microscale heterogeneity and potentially reflecting distinct petrogenetic histories. The EPMA results reveal that clinopyroxenes are compositionally diopside to augite, while amphiboles range from magnesio-hornblende, tschermakite, sadanagaite to pargasite. The LA-ICP-MS analyses allow for the classification of four pyroxene (Px-I to Px-IV) and six amphibole types (Amp-I to Amp-VI). Among these, Px-I, Amp-I, Amp-II, and Amp-IV exhibit relatively primitive geochemical signatures compared to their host rocks. These characteristics are consistent with crystallization from earlier, less evolved magmatic pulses, supporting their interpretation as antecrysts, whereas the others are considered as autocrysts. Thermobarometric calculations reveal that amphiboles in the KKVC suite crystallized at pressures ranging from 0.8 to 5.4 kbar, indicating magma storage across both shallow and deep crustal levels. However, those of clinopyroxenes yield 4-9 kbar and 1025-1116 °C, suggesting derivation from deeper reservoirs. Clinopyroxene P-T calculations for the KPVF basalts indicate high-pressure crystallization (12-14 kbar) at temperatures up to 1266°C, reflecting deep crustal magma storage. All obtained data reveal open-system magma reservoirs with repeated mixing and recharge, triggering Quaternary eruptions and highlighting the role of trans-crustal magmatic system in Central Anatolia.